Nanoparticle-Based Combination Therapy for Melanoma - Chen, Hongbo; Hou, Kai; Yu, Jing; Wang, Le; Chen, Xue (Frontiers in Oncology, 2022)
Melanoma is a cutaneous carcinoma, and its incidence is rapidly increasing with every year. The treatment options for melanoma have been comprehensively studied. Conventional treatment methods (e.g., radiotherapy, chemotherapy and photodynamic therapy) with surgical removal inevitably cause serious complications; moreover, resistance is common. Nanoparticles (NPs) combined with conventional methods are new and promising options to treat melanoma, and many combinations have been achieving good success. Due to their physical and biological features, NPs can help target intended melanoma cells more efficiently with less damage. This creates new hope for a better treatment strategy for melanoma with minimum damage and maximum efficacy.